ANALISIS USAHA AGRIBISNIS INDUSTRI TEMPE KEDELAI RUMAH TANGGA DI KABUPATEN JEMBER - Ratih Rahmawati (STIE Mandala Jember, 2012)
This research was intendend to identify the income of entrepreneurs of soybean-madetempe, analyze the feasibility of business development, calculate the efficiency ofproduction cost and agribusiness development strategy of soybean-made tempe homeindustries. The research was conducted in four villages, namely: Pagah, Tegalboto,Tegalbesar, Kaliputih, Jember Regency.The data used were primary data obtained from entrepreneur respandents and secondarydata from related agencies, the analyses used were income analysis, NPV (Net PresentValue) method, B/C Ratio method. IRR (lnternal Rate of Return), SYVOI (Strengfhs,Weaknesses, Opporlunity, Threat) analysis. The result showed that the income analysis ofsmall-scale buslness resulted higher value than that of large sca/e business, sensifivifyanalysis showed that the increasing prices of raw materids of soybean of small scalebusiness affected the decrease of soybean-made tempe sales.